Unique Catalytic Performance of the Polyoxometalate [Ti2(OH)2As2W19O67(H2O)]8–: The Role of 5-Coordinated Titanium in H2O2 Activation - Kholdeeva, Oxana A. (2009)
Tetra-n-butylammonium (TBA) salts of the dititanium sandwich-type 19-tungstodiarsenate(III) [Ti2(OH)2As2W19O67(H2O)]8– (1) revealed a unique catalytic performance in the selective oxidation of organic compounds with aqueous hydrogen peroxide. The selectivity of alkene oxidation strongly depends on the amount of acidic protons in the cationic part of 1, which can be controlled by pH of precipitation of the TBA salt. Selectivities of almost 100 % were achieved for cyclohexene epoxidation by using TBA5.5Na1.5K0.5H0.5-1. In the presence of TBA5.5K0.5H2-1, cyclohexene epoxide readily transformed into trans-1,2-cyclohexanediol, 2-hydroxycyclohexanone, and C–C bond-cleavage products. No allylic oxidation products were found. Vicinal diols yielded α-hydroxyketones and (di)carboxylic acids. Ketonization of cyclohexanol proceeded with selectivity as high as 98 %, whereas 1-hexanol produced hexanal and hexanoic acid. The oxidation products are consistent with a heterolytic mechanism of H2O2 activation. The stability of 1 under turnover conditions was confirmed by IR spectroscopy. The presence of titanium atoms in the belt of 1 is vital for the catalytic performance. The titanium-free analogue, [As2W21O67(H2O)]6– (2), revealed lower activity and selectivity in the oxidation of alcohols and was not active in the oxidation of alkenes. The catalytic performance of 1 contrasts that of polyoxometalates containing hexacoordinate Ti atoms, for example, TBA7[(PTiW11O39)2OH], TBA8H7[{Ti3PW9O37(OH)}3(PO4)], and TBA17[(α-Ti3SiW9O37OH)3{TiO3(OH2)3}], for which a homolytic oxidation mechanism was manifested by the formation of cyclohexene allylic oxidation products. The unique ability of 1 to catalyze heterolytic oxidations with the use of hydrogen peroxide most likely originates from the specific coordination number (5) and geometry (square-pyramidal) of the Ti atoms in this polyanion.(© Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2009)